How do voters respond to information on self-serving elite behaviour? Evidence from a randomized survey experiment in Tanzania - Ivar Kolstad; Arne Wiig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Does self-serving elite behaviour make citizens more politically active? This paper presents the results of a randomized field experiment where voters in Tanzania were given information about elite use of tax havens. Information provided in a neutral form had no effect on voting intentions. Information phrased in more morally charged terms led to a reduction in voting intentions. Additional evidence suggests that rather than increase the perceived importance of voting, charged information tends to undermine confidence in political institutions and the social contract. The effects are particularly pronounced among the less well-off, indicating that increased transparency in the absence of perceived agency may not improve democratic accountability.
Keywords: C93; D72; H11; H26; 330; elites; citizens; voter turnout; political participation; tax havens; political economy